Liberalization of the Thai energy sector: A consideration of competition law and sectoral regulation - Wisuttisak,P. (Oxford University Press, 2015)
The article explores the policy of liberalization in the Thai energy sector and identifies problems in Thai competition law and sectoral regulation contributing to a lack of competitive development in the Thai energy sector. The article also proposes possible plans for improving both competition law and sectoral regulation to facilitate the move towards competition in the Thai energy sector. In the first part, the article provides an overview of the liberalization and market reform process which has lead to the current uncompetitive structure of the Thai energy sector. In the second part, the article describes the problems of Thai competition law and sectoral regulation, relating to the Thai energy markets. It explores the problems of ineffective competition law and energy regulation which is unable to deal with an uncompetitive structure under the control of state-owned enterprises. In the third part, the article provides suggestions for the development of competition in the Thai energy sector. © The Authors 2012. Published by Oxford University Press on behalf of the AIPN. All rights reserved.